Kinetics of casein hydrolysis by peptidase from Bacillus thuringiensis var. israelensis - O. V. Sevastyanov; Yu. A. Shesterenko; A. A. Ryzhak; I. I. Romanovska; N. A. Dziubliuk; L. D. Varbanets (The Ukrainian Biochemical Journal, 2019)
The kinetics of enzyme reaction is generally studied using the Michaelis-Menten equation and various methods of its linearization. Each method has its advantages and drawbacks, so their comparison for determining the kinetics of new enzymes action is topical. The aim of this work was to study the kinetics of casein hydrolysis catalyzed by new peptidase from Bacillus thuringiensis var. israelensis IMB B-7465 using several methods of enzyme activity assessment and Michaelis-Menten equation linearization. The satisfactory agreement between kinetic constants values obtained by the methods of Lineweaver-Burk, Hanes, Eadie-Hofstee, Cornish-Bowden-Eisenthal was established. The Lineweaver-Burk method was shown to be optimal for determining Km and Vmax of casein hydrolysis. Estimation of caseinolytic activity with the use of ortho-phthalic dialdehyde allowed more accurate Vmax determination compared to the use of Anson and Kunitz methods.